2020
DOI: 10.3892/ol.2020.11516
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑758 acts as a tumor inhibitor in colorectal cancer through targeting PAX6 and regulating PI3K/AKT pathway

Abstract: Recently, a number of microRNAs (miRNAs) have been reported to play different roles in human cancers, including colorectal cancer (CRC). However, the specific role of miR-758 has not been clarified in CRC. Therefore, the aim of the present study was to explore the role of miR-758 in CRC. RT-qPCR and western blot analysis were used to quantify the expression of miR-758 and genes. The function of miR-758 in CRC was investigated using Transwell, CCK-8 and luciferase reporter assays. According to the results, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…miR‐758‐3p exhibited a tumor‐suppressive role in human cancers, including non‐small cell lung cancer, bladder cancer, cervical cancer, papillary thyroid cancer, colorectal cancer and breast cancer 14 15 , 27–30 Moreover, miR‐758‐3p could restrain cell proliferation and increase apoptosis in AML 16 . Similarly, we also validated the anti‐leukemogenic function of miR‐758‐3p, and found circ_0002483 could control AML progression by modulating miR‐758‐3p.…”
Section: Discussionmentioning
confidence: 54%
“…miR‐758‐3p exhibited a tumor‐suppressive role in human cancers, including non‐small cell lung cancer, bladder cancer, cervical cancer, papillary thyroid cancer, colorectal cancer and breast cancer 14 15 , 27–30 Moreover, miR‐758‐3p could restrain cell proliferation and increase apoptosis in AML 16 . Similarly, we also validated the anti‐leukemogenic function of miR‐758‐3p, and found circ_0002483 could control AML progression by modulating miR‐758‐3p.…”
Section: Discussionmentioning
confidence: 54%
“…PAX6 is also involved in a variety of key biological processes, including cell proliferation, migration, adhesion, signal transduction in normal development and tumorigenesis [ 29 , 30 ]. PAX6 showed the most interactions in the largest network, and has been reported to be a cancer driver in various cancers including lung [ 31–33 ] breast [ 30 ], colon [ 34 , 35 ], liver [ 36 ], pancreatic [ 36 ], and thyroid cancers [ 37 ]. Studies have shown that forced expression of PAX6 induces the formation of retinal heterotopic tissue [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that EG1 has an inhibitory effect on PAX6 as this protein has sequence homology with PAX2 and is expressed in HCT116 cells ( Figure 4 ). Furthermore, differing levels of PAX6 have been shown to regulate cell cycle progression in colorectal cancer cells with high levels leading to an increase in cell proliferation ( 31 ) through the modulation of PI3K/AKT signalling ( 32 ). It is therefore plausible that EG1 could also affect proliferation via PAX6.…”
Section: Discussionmentioning
confidence: 99%